2013
DOI: 10.3791/50247
|View full text |Cite
|
Sign up to set email alerts
|

Direct Pressure Monitoring Accurately Predicts Pulmonary Vein Occlusion During Cryoballoon Ablation

Abstract: Cryoballoon ablation (CBA) is an established therapy for atrial fibrillation (AF). Pulmonary vein (PV) occlusion is essential for achieving antral contact and PV isolation and is typically assessed by contrast injection. We present a novel method of direct pressure monitoring for assessment of PV occlusion.Transcatheter pressure is monitored during balloon advancement to the PV antrum. Pressure is recorded via a single pressure transducer connected to the inner lumen of the cryoballoon. Pressure curve characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 10 publications
2
22
2
Order By: Relevance
“…In prior research, the accuracy of pressure monitoring in detecting PV occlusion was confirmed in 46 of 47 veins by TEE‐CFD, but we only confirmed complete occlusion in 43 of 67 veins (64%). Kosmidou et al supported the accuracy of pressure monitoring, because their success rate was equivalent to those found in other studies; however, our study showed that PV pressure monitoring had only a 64.1% positive predictive value, so we could not reach the same conclusion.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In prior research, the accuracy of pressure monitoring in detecting PV occlusion was confirmed in 46 of 47 veins by TEE‐CFD, but we only confirmed complete occlusion in 43 of 67 veins (64%). Kosmidou et al supported the accuracy of pressure monitoring, because their success rate was equivalent to those found in other studies; however, our study showed that PV pressure monitoring had only a 64.1% positive predictive value, so we could not reach the same conclusion.…”
Section: Discussioncontrasting
confidence: 74%
“…In our study, we examined the accuracy of monitoring pressure changes recorded from the distal tip of inflated balloon in predicting PV occlusion (with angiography as the standard for comparison). We recorded pressure changes from LA to PA in 67 of 72 veins (93%), which is comparable to what other published studies have found . In contrast to Siklódy et al., we could not confirm the accuracy of pressure monitoring in assessing complete PV occlusion during cryoballoon ablation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…With this background, Siklódy et al initially reported that the PV occlusion well correlated with the changes in the pressure curve recorded from the distal tip of the CB catheter and that this technique could be applied to the first‐generation CB‐PVI procedure. Other pilot and small observational studies showed that additional pressure curve monitoring significantly reduced the contrast volume utilization (23 and 8 mL) as compared to the conventional strategy in the first‐generation CB‐PVI . The present study had three major differences from the prior studies .…”
Section: Discussionmentioning
confidence: 62%
“…In this issue of the journal, Hasegawa et al report the results of a prospective randomized study with a comparison of the pressure‐wave approach as an alternative modality to assess pulmonary vein (PV) occlusion and the conventional strategy of contrast injection to guide cryoballoon PV isolation. The authors need to be applauded for having shown the value of this alternative technique, only described elsewhere in a anecdotal fashion or small clinical studies …”
mentioning
confidence: 99%